PERMAINAN PERILAKU BAIK (GOOD BEHAVIOR GAME) DALAM UPAYA PENCEGAHAN BULLYING - M.Elyas Arif Budiman; Zidni Nuris Yuhbaba; Wahyi Sholehah Erdah Suswati; Wike Rosalini (Jurnal SADEWA, 2026)
Bullying is the act of intentionally and repeatedly hurting, degrading, or oppressing others, whether physically, verbally, socially, or psychologically. Bullying usually occurs in relatively unstructured situations and areas with minimal supervision such as schools. Good behavior game activities are packaged in the form of community service activities with the aim of controlling and preventing bullying in schools. Good behavior games are a group-based classroom behavior management strategy that encourages classmates' concern for each child's behavior by giving awards to teams that demonstrate levels of inappropriate behavior and lead to bullying. This activity was attended by 25 elementary school students. The results of the study showed that the level of student knowledge before the activity was 48% in the poor knowledge category and after being given the good behavior game activity, student knowledge increased to good knowledge by 64%.). Good behavior games can be one of the effective games and can be used by teachers as anti-bullying learning